2018
DOI: 10.3390/rs10020257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multi-Frequency SAR Images for Tropical Land Cover Mapping

Abstract: Earth Observation (EO) data plays a major role in supporting surveying compliance of several multilateral environmental treaties, such as UN-REDD+ (United Nations Reducing Emissions from Deforestation and Degradation). In this context, land cover maps of remote sensing data are the most commonly used EO products and development of adequate classification strategies is an ongoing research topic. However, the availability of meaningful multispectral data sets can be limited due to cloud cover, particularly in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
0
15
0
1
Order By: Relevance
“…[38][39][40] One way to make use of the sensitivity of microwaves toward different scattering mechanisms is the utilization of sensors that employ different frequencies. 41 While combinations of short and long microwaves have been successfully applied for forest biomass estimates, 42,43 only Srivastava et al 44 and Herold et al 45 confirmed their potential for thin vegetation layers. Integrating passive radar for large-scale mapping is mostly limited to soil moisture 46 or surface temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] One way to make use of the sensitivity of microwaves toward different scattering mechanisms is the utilization of sensors that employ different frequencies. 41 While combinations of short and long microwaves have been successfully applied for forest biomass estimates, 42,43 only Srivastava et al 44 and Herold et al 45 confirmed their potential for thin vegetation layers. Integrating passive radar for large-scale mapping is mostly limited to soil moisture 46 or surface temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to how SAR and multi-spectral imaging provide information about different physical properties of features on the ground, SAR sensors operating at different frequencies (e.g., Table S2) provide different information due to the role of the SAR wavelength in influencing interactions of the microwave with scatterers of different sizes, the scattering mechanism (direct, double-bounce, volumetric: Section 2) and the penetration of the radar signal into the volume of ground targets. Different SAR frequency bands can be integrated for improving, e.g., LUCC classification accuracy (e.g., [24,89]), and there is currently scope to test a larger SAR frequency range than ever before with imagery now available at C-band (Sentinel-1), X-band (commercial providers), L-band (commercial providers but with future open-access from the NISAR mission due for launch in 2021, plus other missions such as ESA's ROSE-L in due course) and S-band (NovaSAR-1).…”
Section: Synergies Between Sar and Other Eo Data Types For Hazard Monitoringmentioning
confidence: 99%
“…The Office of Space and Terrestrial Applications-1 and -3 (OSTA-1/OSTA-3) payloads flying on NASA Space Shuttle missions STS-2 and STS41G in the years 1981 and 1984 carried the experimental L-band SAR instruments Shuttle Imaging Radar-A (SIR-A) and Shuttle Imaging Radar-B (SIR-B). The Spaceborne Imaging Radar-C, X-Band Synthetic Aperture Radar (SIR-C/X-SAR) payload was launched on the Space Shuttle Endeavour for two ten-day missions in the spring and fall of 1994 and provided the first spaceborne, multi-frequency (L-, C-X-band) SAR datasets [92][93][94].…”
Section: Spaceborne L-band Sar Systemsmentioning
confidence: 99%